2013
DOI: 10.1007/s10552-013-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

Men with prostate cancer make positive dietary changes following diagnosis and treatment

Abstract: Around one-third of men spontaneously adopted a healthier diet and also consumed more 'prostate-healthy' foods following a diagnosis of PC. Dietary choices also differed by radical or monitoring treatments, indicating that men undergoing active surveillance may be more likely to pursue dietary changes as an adjunct therapy. PC survivors can adopt healthier diets, thus providing clinicians with opportunities to support PC survivorship by providing targeted advice beneficial to general and potentially prostate-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 24 publications
3
74
0
Order By: Relevance
“…This supports findings from an interview study in which PC patients focused on diet as an adjunct therapy and self-management strategy to overcome AS-related anxiety, though there were no comparisons with radical treatments [25]. Recent research from the ProtecT trial further shows that men undergoing AM consumed more fruit/vegetable juice (including tomato juice) than those randomised to surgery [21]. …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This supports findings from an interview study in which PC patients focused on diet as an adjunct therapy and self-management strategy to overcome AS-related anxiety, though there were no comparisons with radical treatments [25]. Recent research from the ProtecT trial further shows that men undergoing AM consumed more fruit/vegetable juice (including tomato juice) than those randomised to surgery [21]. …”
Section: Discussionsupporting
confidence: 52%
“…increased fruit and vegetables, decreased fat and red meat). Recent findings from food questionnaire data from ProtecT showed that a PC diagnosis prompted one third of men to adopt healthier diets [21]. …”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that some control group AS patients pursued lifestyle changes. Men participating in the Prostate Testing for Cancer and Treatment (ProtecT) randomised trial of active monitoring (a surveillance strategy), radical prostatectomy, and radiotherapy, generally made healthy dietary changes following diagnosis (eg, less red meat) with greater changes made by those on active monitoring [45].…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Although some research suggests that UK men are interested in diet improvements as part of prostate cancer supportive care, (Avery et al, 2014) there is currently little research or services available to address this need for nutrition education and interventions. Consequently, little is known about what features of diet interventions would best contribute to changing men's diets favourably after a prostate cancer diagnosis (Demark--Wahnefried, 2009;Avery 2013;Carmody 2012).…”
Section: Introductionmentioning
confidence: 99%